Community Empowerment Program in Jepara Regency Perceived by Social Capital and Islamic Values - Ahmad Kharis; Sriharini Sriharini; Mutrofin Mutrofin (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
Social capital has an important role that influencing social dynamics in agroup and functions as external work and internal power that influencedthe success of the program. Likewise, social capital affects the success ofan existing empowerment program in the community. The purpose of thispaper is to examine the empowerment program in Sumber Rejo CattleGroup through social capital and Islamic values and perspective. This studyused a qualitative method with data sampling from an informant whocomes as a member of the Sumber Rejo Cattle group and the governmentas stakeholders in this program. The result showed that the conception ofsocial capital as a resource for action is one way of introducing socialstructure into the rational action paradigm. Three forms of social capitalare examined: obligations and expectations, information channels, andsocial norms. Despite, low social capital caused by violations of cooperationagreements, lack of communication, and anomalies in the formation ofother groups caused the program being stagnated. On the other hand, Islamprovides solutions to prevent the stagnation of this program, by proceededinclusive moral values, establishing friendships, and maintaining trust inthe all of members.